Hubungan Ekspresi Protein Bcl-2 Jaringan dengan Disease Free Survival 2 Tahun Pasien Kanker Epitel Ovarium di Rumah Sakit Dr. Soetomo, Surabaya - K, ARDHANU (Indonesian Journal of Cancer, 2015)
ABSTRACTOvarian cancer is one of the most common causes of death among gynecological malignancies. Previous reports have shown that the anti-apoptotic protein Bcl-2 is over expressed in many solid neoplasms, including ovarian cancers, and contributes to neoplastic transformation and drug-resistant disease, resulting in poor clinical outcome. This study is an observational descriptive cross-cut design to determine the role of Bcl-2 protein expression as a two year disease free survival prognostic factor in patients with epithelial ovarian cancer. Data were extracted from 37 patients treated with primary surgery with or with out secondary surgery followed by adjuvant therapy, from January 1st2010 to December 31st2011, at the Division of Gynecologic Oncology, Department of Obstetric and Gynecology, Medical Faculty of Airlangga University, Surabaya, Indonesia, were retrospectively analyzed. Bcl-2 expression were analized by immunohistochemistry study. The reccurency evaluation was done by CT-scan. The time to follow-up was 24 months since patients diagnosis. Spearman and Phi correlation test were used for analysis. In this study, two year disease free survival rate of patients was found 78.4% (29 of 37), respectively, and Spearman and Phi correlation test showed that there were no significant relation between Bcl-2 expression and ovarian cancer recurrence (p=0.084). Expression of Bcl-2 as an anti-apoptotic protein in ovarian cancer was not significantly related with the tumor reccurency as a marker of the two year disease free survival.Keyword: ovarian cancer, Bcl-2 protein expression, two year disease free survivalÂ ABSTRAKKanker ovarium merupakan salah satu penyebab terbanyak kematian karena kanker ginekologi. Penelitan sebelumnya menunjukkan bahwa protein anti-apoptosis Bcl-2 ter-over-expressed pada banyak neoplasma solid, termasuk kanker ovarium; juga berkontribusi pada transformasi neoplasma dan resistansi terhadap kemoterapi yang menyebabkan luaran klinis kurang baik. Ini adalah penelitian observasional deskriptif dengan rancangan potong silang untuk melihat peran ekspresi protein Bcl-2 sebagai faktor prognostik disease free survival 2 tahun pada pasien kanker epitel ovarium. Data diambil dari 37 pasien yang menjalani operasi primer dengan/tanpa operasi sekunder yang diikuti dengan kemoterapi ajuvan, dari 1 Januari 2010 sampai dengan 31 Desember 2011, di Divisi Onkologi Ginekologi, Departemen Obstetri dan Ginekologi, Fakultas Kedokteran Universitas Airlangga, Surabaya, Indonesia, dianalisis secara retrospektif. Ekspresi Bcl-2 diperiksa dengan teknik histokimia. Evaluasi rekurensi dilakukan dengan pemeriksaan CT-scan. Pemeriksaan dilakukan pada pasien yang sudah 2 tahun terdiagnosis kanker ovarium. Uji korelasi Spearman dan Phi dipergunakan untuk analisis data. Hasil penelitian menunjukkan angka bebas tumor 2 tahun sebesar 78,4% (29 dari 37), dan uji korelasi Spearman serta Phi menunjukkan bahwa tidak ada hubungan yang bermakna antara Bcl-2 dengan angka bebas tumor yang ditunjukkan dengan rekurensi tumor (p=0,084). Kesimpulannya, ekspresi protein sebagai protein anti-apoptosis pada kanker ovarium tidak berhubungan secara bermakna dengan rekurensi tumor sebagai petanda angka bebas tumor 2 tahun.Kata Kunci: kanker ovarium, ekspresi protein Bcl-2, angka bebas tumor 2 tahun.